Hypoglycemic effect of water extract of the root of Pandanus odorus RIDL - Penchom Peungvicha (2018)
Hypoglycemic effect of water extract of the root of Pandanus odorus RIDL. (Thai name: Toei-hom, Pandanaceae) was examined in normal and streptozotocin-diabetic rats. In the hypoglycemic test without glucose load, an administration of the extract at doses of 0.125-0.5 g/kg p.o. did not affect significantly the plasma glucose level in normal rats, whereas the extract significantly lowered the plasma glucose level at a dose of 0.5 g/kg p.o in diabetic rats. In oral glucose tolerance test, an administration of the extract at a dose of 0.5 g/kg p.o. significantly lowered the plasma glucose level in normal rats. The extract at doses of 0.5 and 1.0 g/kg p.o. also significantly lowered the plasma glucose level in diabetic rats. A reference drug, glibenclamide at a dose of 5 mg/kg p.o. showed a significant hypoglycemic effect in both normal and diabetic rats. Repeated administration of the extract at doses of 0.25 and 0.5 g/kg p.o. for 7d produced a significant hypoglycemic effect in diabetic rats. Glibenclamide (5 mg/kg p.o.) also caused a significant hypoglycemia in the diabetic rats. LD50(95% confidence limit) after intraperitoneal injection was 1.87 (1.26-2.76) g/kg in male and female rats and 1.62 (1.18-2.24) g/kg in male and female mice, respectively. The LD50after oral administration was over 8 g/kg in both sexes of rat and mice.